2015
DOI: 10.12693/aphyspola.128.283
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Electrical Characterization of (002)-Preferentially Oriented n-ZnO/p-Si Heterostructure

Abstract: In this paper, preferentially oriented (002) ZnO thin lms have been grown on Si (100) and glass substrates using radio frequency magnetron sputtering. The dependence of the quality of the ZnO thin lms at dierent substrate temperatures on the growth is studied. A ZnO thin lm with c-axis-oriented würtzite structure is obtained at a growth temperature from 200 to 400• C. X-ray diraction shows that the full width at half maximum θ2θ of (002) ZnO/Si is located at approximately 34.42• , which is used to infer the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 30 publications
1
15
1
Order By: Relevance
“…The increase in the film thickness leads to an improvement of the crystalline quality. This is attributed to the strain in the film introduced during the deposition [34], that is, the thicker films suffer less strain than the thinner ones. This comes in a good agreement with our results where thicker films have lower stress value and better quality.…”
Section: Xps Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in the film thickness leads to an improvement of the crystalline quality. This is attributed to the strain in the film introduced during the deposition [34], that is, the thicker films suffer less strain than the thinner ones. This comes in a good agreement with our results where thicker films have lower stress value and better quality.…”
Section: Xps Studymentioning
confidence: 99%
“…It has been observed that the average transmittance of the studied samples in the visible range decreased from 40% to 20% with increased film thickness. The optical transmittance provides useful information about the optical band gap of the semiconductor [34] as shown in Figure 6.…”
Section: Opticalmentioning
confidence: 99%
“…The optical transmittance provides useful information about the optical band gap of a semiconductor 31 . It was observed that the average transmittance of samples in the visible and near infrared range is varied from 80% to 92%.…”
Section: Optical Measurementsmentioning
confidence: 99%
“…Also, it has been demonstrated that the increased in substrate temperature accompanied with improvement of ZnO film quality, could be led to extract the band gap of 3.2 eV at 400°C by recording the UV-Vis transmittance spectra. The C-V and I-V measurements on the basis of the heterojunction thermal emission model have confirmed that the domination of high-density grain boundary layer existing at the region of interfacing [6].…”
Section: Introductionmentioning
confidence: 57%
“…Also, new thin films were prepared by DC magnetron sputtering, it was found that the films have a corrosion resistance with high microhardness value [5]. The NLO properties of ZnO films are currently subject to specific work, in response to satisfy the industrial need for optoelectronic devices, it could be operated at a short wavelengths range [6]. Pure and doped nanocrystalline ZnO films have shown high second-harmonic efficiency and this makes the ZnO to be used as efficient optical modulator [7].…”
Section: Introductionmentioning
confidence: 99%